Synthesis of fluorene-based di-BODIPY dyes containing different aromatic linkers and their properties. Issue 52 (30th December 2015) - Zhao, Hongbin; Liao, Junxu; Peng, Min; Wang, Yucai; Zhou, Weinan; Li, Bohong; Shen, Songping; Xie, Zechuan
Graphical abstract: Abstract: Three novel fluorene-based symmetric di-BODIPY dyes (BDPa–c ) featuring a fluorene motif as the central core, BODIPY as the terminal groups, and several types of aromatic groups, including phenyl, thiophene, and furan, as linkers were synthesized. The optical and electrochemical properties of these BODIPY dyes were investigated, and DFT theoretical calculations were performed. All these dyes show absorption bands in the region of 300–650 nm with high extinction coefficients. Furan-linked dyeBDPc exhibit a more coplanar molecular structure, which increases the efficient π-conjugation length and causes intensive intramolecular charge transfer (ICT), resulting in broadened and red-shifted absorption bands. The luminescence of these dyes is located in near-infrared regions with large Stokes shifts (1013–4862 cm −1 ). The HOMO/LUMO energy levels, as investigated by CV are approximately 5.5 eV and 3.6 eV, respectively.